(untitled) (Bulletin of Innovative Research, 2026)
The article is devoted to the analysis of lexical variants in the modern Russian language as one of the manifestations of the dynamics of the language system. The concept of lexical variability, its main types, causes of occurrence, and functioning in different spheres of speech are considered. The paper analyzes examples of lexical variability in the literary language, colloquial speech, and dialects. It is noted that the stability and change of lexical units may depend on territorial and historical factors, which is confirmed by studies of dialect vocabulary of the Russian language. The research results make it possible to identify modern trends in the development of the lexical system of the Russian language and determine the role of variability in language norm and speech practice.